2011
DOI: 10.1007/s11095-011-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of the Inhibitory Effects of Naproxen on the Time-Courses of Inflammatory Pain, Fever, and the Ex Vivo Synthesis of TXB2 and PGE2 in Rats

Abstract: Due to better sensitivity and similar drug-induced inhibition, the biomarker PGE(2) and the antipyretic effect would be suitable alternative endpoints to the analgesic effects for characterization and comparisons of potency and time-courses of drug candidates affecting the COX-2 pathway and to support human dose projections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…No delay in the onset of inhibition was observed, revealing that the effect compartment was located in the central compartment. This result agrees with a previous report that described the use of naproxen [14,23] .…”
Section: Wwwchinapharcom Zhang J Et Alsupporting
confidence: 93%
See 1 more Smart Citation
“…No delay in the onset of inhibition was observed, revealing that the effect compartment was located in the central compartment. This result agrees with a previous report that described the use of naproxen [14,23] .…”
Section: Wwwchinapharcom Zhang J Et Alsupporting
confidence: 93%
“…Due to the possibility of repeated measurements and increased reproducibility and sensitivity, PGE 2 could be a suitable alternative endpoint for investigations and comparisons of the time-course and potency of various drug candidates [23] . Several reports have shown the integrated PK-PD modeling of NSAIDs using hyperthermia, hyperalgesia, edema or PGE 2 as pharmacological endpoints [5,11,23] , but little attention has been paid to the impact of the disease status on drug effects [16] . The aim of this study was to characterize the PK-PD modeling of diclofenac in normal and FCA-induced arthritic rats using PGE 2 as a pharmacological endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Ketorolac and naproxen are clinically available NSAIDs that non-selectively inhibit COX enzyme activity and the metabolites like prostaglandin E2 thereby blocking inflammation-induced pain (Buckley and Brogden 1990; Krekels et al 2011). The third part of the studies showed that both ketorolac and naproxen were effective in attenuating carrageenan-induced hyperalgesia in a dose dependent manner.…”
Section: Methodsmentioning
confidence: 99%
“…For example, concentrations of prostaglandin E 2 (PGE 2 ) and thromboxane B 2 (TXB 2 ) are often quantified as indicators for COX-2 and COX-1 activities. 24,25 Proinflammatory cytokines, such as TNFα and IL-1β, are widely used biomarkers for many therapeutic agents. 2632 Measurement of target cytokine concentrations of anticytokine therapeutics allows direct assessment of their PK/PD.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…The first is use of immunoassays, such as enzymelinked immunosorbent assays (ELISAs) 2831,3335 and radioimmunoassay (RIA), 36 and the other is ex vivo measurement of enzyme activity. 24,25,37 When measurement of protein concentrations of the mediators is not feasible (usually due to assay insensitivity), mRNA concentrations may be obtained by polymerase chain reaction (PCR) and used as a surrogate. 26,27 …”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%